Basal Cell Carcinoma: From the Molecular Understanding of the Pathogenesis to Targeted Therapy of Progressive Disease. (12th October 2010) - Göppner, Daniela; Leverkus, Martin
Abstract : Due to intensified research over the past decade, the Hedgehog (HH) pathway has been identified as a pivotal defect implicated in roughly 25% of all cancers. As one of the most frequent cancer worldwide, the development of Basal cell carcinoma (BCC) due to activation of the HH pathway has been convincingly demonstrated. Thus the discovery of this central tumor-promoting signalling pathway has not only revolutionized the understanding of BCC carcinogenesis but has also enabled the development of a completely novel therapeutic approach. Targeting just a few of several potential mutations, HH inhibitors such as GDC-0449 achieved already the first promising results in metastatic or locally advanced BCC. This paper summarizes the current understanding of BCC carcinogenesis and describes the current "mechanism-based" therapeutic strategies.